Detection of antibodies against Paracoccidioides brasiliensis melanin in vitro and in vivo studies during infection (2011)
ABSTRACT: Several cell wall constituents, including melanins or melanin-like compounds, have been implicated in the pathogenesis of a wide variety of microbial diseases caused by diverse species of pathogenic bacteria, fungi, and helminthes. Among these microorganisms, the dimorphic fungal pathogen Paracoccidioides brasiliensis produces melanin in its conidial and yeast forms. In the present study, melanin particles from P. brasiliensis were injected into BALB/c mice in order to produce monoclonal antibodies (MAbs). We identified five immunoglobulin G1 (IgG1) _-chain and four IgM melanin-binding MAbs. The five IgG1 _-chain isotypes are the first melanin-binding IgG MAbs ever reported. The nine MAbs labeled P. brasiliensis conidia and yeast cells both in vitro and in pulmonary tissues. The MAbs cross-reacted with melanin-like purified particles from other fungi and also with commercial melanins, such as synthetic and Sepia officinalis melanin. Melanization during paracoccidioidomycosis (PCM) was also further supported by the detection of IgG antibodies reactive to melanin from P. brasiliensis conidia and yeast in sera and bronchoalveolar lavage fluids from P. brasiliensisinfected mice, as well as in sera from human patients with PCM. Serum specimens from patients with other mycoses were also tested for melanin-binding antibodies by enzyme-linked immunosorbent assay, and crossreactivities were detected for melanin particles from different fungal sources. These results suggest that melanin from P. brasiliensis is an immunologically active fungal structure that activates a strong IgG humoral response in humans and mice.